Association of glycosylated haemoglobin HbA1c levels with outcome in patients with COVID‐19: A Retrospective Study. Issue 7 (10th March 2021) - Yuan, Shuai; Li, Huaping; Chen, Chen; Wang, Feng; Wang, Dao Wen
Abstract: Patients with hyperglycemia tend to be susceptible to Coronavirus disease 2019 (COVID‐19). However, the association of HbA1c level with outcome of COVID‐19 patients was unclear. We performed a retrospective study of 2880 cases of COVID‐19 admitted in Tongji Hospital, Wuhan, China, among which 922 had detected the HbA1c levels. We found that COVID‐19 patients with either lower levels of HbAlc (3%‐4.9%) or higher levels of HbAlc (≥6%) were associated with elevated all‐cause mortality. Meanwhile, we observed that HbAlc levels were highly correlated with haemoglobin (Hb) and total cholesterol (TC) ( P < .0001), moderately correlated with albumin (ALB) and high‐sensitive C reaction protein (hs‐CRP) (0.0001 < P <.001), and relatively low correlated with low‐density lipoprotein cholesterol (LDL‐C) (.001 < P <.01). These associated cofactors might together contribute to the clinical outcome of COVID‐19 patients. Furthermore, the mortality was higher in COVID‐19 patients with newly diagnosed diabetes mellitus (DM) compared with COVID‐19 patients with history of DM. Moreover, in patients with history of DM, the mortality was decreased in patients treated with anti‐hyperglycaemic drugs. In summary, our data showed that the in‐hospital mortality was increased in COVID‐19 patients with lower or higher levels of HbAlc. Meanwhile, initiation of appropriate anti‐hyperglycaemic treatment might improve the clinical outcome in COVID‐19 patients.